Implementasi Forward Chaining dan Certainty Factor pada Aplikasi Konsultasi Kecantikan - Bunga Ratna Sari; Sabar Rudiarto (JITCE (Journal of Information Technology and Computer Engineering), 2021)
Having skin that is free from problems is a dream for most women, especially in Indonesia. However, the problem is not all women are aware that in carrying out treatment or using a product, it must match the needs of each skin type. The rise of beauty salons that operate but are not under the auspices of specialist doctors and also cheap beauty products that are claimed to solve skin problems in an instant makes women easily tempted. This of course can have a big negative impact when the maintenance procedures performed are not up to standard, and there are dangerous ingredients in the products used. For this reason, consulting with a specialist or the expert is indispensable. Researchers used the forward chaining method and certainty factors in building this system which is expected to be used in determining facial skin problems and their solutions based on case studies at the XYZ beauty clinic. The Forward Chaining method is used to draw conclusions based on the facts entered. While certainty factor is used to calculate the trust value from the existing conclusions. This method requires 2 main values ​​in performing calculations, namely MB (measurement of belief) and MD (measurement of disbelief). Based on the research that has been done, the system was successfully built and gave an accuracy value of 97.35%.